please answer for this question fastly
Attachments:
![](https://hi-static.z-dn.net/files/de1/979eebdaa374b1b90f721ac06e1996fa.jpg)
Answers
Answered by
1
given,
p(x)=2x^4-5x^2-7x+5
q(x)=2x^3-3x+4
so, p(x)=2x^4+0x^3-5x^2-7x+5
q(x)=2x^3+0x^2-3x+4
now add both and subtract and again you substitute the value of x as 1.
hope this will help u
p(x)=2x^4-5x^2-7x+5
q(x)=2x^3-3x+4
so, p(x)=2x^4+0x^3-5x^2-7x+5
q(x)=2x^3+0x^2-3x+4
now add both and subtract and again you substitute the value of x as 1.
hope this will help u
Similar questions